PENGARUH PENINGKATAN MUTU SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS KOPERASI DAN UMKM PROVINSI SULAWESI SELATAN - Basri Basir MR; Andi Jam’an; Reski Amalia (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2021)
This study aims to determine the partial effect of improving the quality of human resources on employee performance at the Office of Cooperatives and SMEs in South Sulawesi Province. The data collection technique in this study was a questionnaire. The population in this study were all employees of the Office of Cooperatives and SMEs in South Sulawesi Province, amounting to 120 people with a simple random sampling of 50 people. The type of research used is quantitative, with simple linear regression testing, by testing the validity and reliability of the statement items for each variable and the T test which is processed using the IBM SPSS Statistics V.28 program. The results showed that improving the quality of human resources had a significant effect on employee performance at the Office of Cooperatives and SMEs in South Sulawesi Province. This means that the better the improvement in the quality of human resources carried out at the South Sulawesi Province Cooperatives and SMEs Office, the better the performance of employees at the South Sulawesi Province Cooperatives and SMEs Office.